1999
DOI: 10.1046/j.1365-2672.1999.00883.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence, assembly and analysis of pX01 and pX02

Abstract: . Bacillus anthracis plasmids pX01 and pX02, harboured by the Sterne and Pasteur strains, respectively, have been sequenced by random 'shotgun' cloning and high throughout sequence analysis. These sequences have been assembled (Sequencher) to generate a circulate pX01 plasmid containing 181 656 bp and a single linear (gapped) pX02 contig containing at least 93·479 bp. Initial annotation suggests that the two plasmids combined contain at least 200 potential open reading frames (ORFs) with ³ 40% having significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
129
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(130 citation statements)
references
References 4 publications
0
129
0
1
Order By: Relevance
“…However, in the case of TnPpa1, transposition is responsible for the movement of the element. The same mechanism of translocation is also suggested for a 44?8 kb long pathogenicity island of Bacillus anthracis which is flanked by inverted copies of IS1627 (Okinaka et al, 1999).…”
Section: Discussionmentioning
confidence: 81%
“…However, in the case of TnPpa1, transposition is responsible for the movement of the element. The same mechanism of translocation is also suggested for a 44?8 kb long pathogenicity island of Bacillus anthracis which is flanked by inverted copies of IS1627 (Okinaka et al, 1999).…”
Section: Discussionmentioning
confidence: 81%
“…Since main differences between members of the B. cereus group have been attributed to their plasmids (Okinaka et al, 1999;Rasko et al, 2005;Schnepf et al, 1998), the DNA of 29 B. cereus group plasmids was also scanned for genes encoding TCSs. Surprisingly, only plasmid pBc10987 of B. cereus ATCC 10987 appeared to encode a TCS, while one 'orphan' RR was found on the megaplasmid pE33L466 of B. cereus ZK (results not shown).…”
Section: Initial Identification Of Hks and Rrsmentioning
confidence: 99%
“…Members of the B. cereus group form a highly homogeneous subdivision within the genus Bacillus and it has been proposed that B. cereus, B. thuringiensis and B. anthracis are in fact varieties of the same species (Daffonchio et al, 2000;Helgason et al, 2000). However, B. anthracis and B. thuringiensis differ from B. cereus by containing plasmid-encoded specific toxins and a capsule (B. anthracis only) (Okinaka et al, 1999;Schnepf et al, 1998) and recent studies have shown that B. anthracis is rather monomorphic, whereas there is large diversity within B. cereus and B. thuringiensis (Bavykin et al, 2004;Hill et al, 2004;Priest et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, B. anthracis is the etiologic agent of anthrax, an acute fatal disease among mammals, which in recent years has become known for its use as a biological weapon (6). The genes encoding the major anthrax toxins and the poly-␥-D-glutamic acid capsule are located on two virulence plasmids, pXO1 (182 kb) and pXO2 (96 kb), respectively, and are required for full virulence (7)(8)(9).…”
mentioning
confidence: 99%